Supplementation with spinach-derived thylakoid augments the benefits of high intensity training on adipokines, insulin resistance and lipid profiles in males with obesity - Saeidi, Ayoub; Saei, Mohammad Amin; Mohammadi, Behnam; Zarei, Hamid Reza Akbarzadeh; Vafaei, Morvarid; Mohammadi, Amir Shayan; Barati, Masoumeh; Montazer, Mona; Razi, Omid; Kiyumi, Maisa Hamed Al; Laher, Ismail; Gholami, Mandana; et al. (Frontiers in Endocrinology, 2023)
This study investigated the effects of 12 weeks of high-intensity functional training (HIFT) combined with spinach-derived thylakoid supplementation on some selected Adipokines and insulin resistance in males with obesity. Sixty-eight participants (mean age: 27.6±8.4 yrs.; mean height: 168.4±2.6 cm; mean weight: 95.7±3.8 kg, mean BMI: 32.6±2.6 kg/m2) were randomly divided into four groups of 17 per group: Control group (CG), Supplement group (SG), Training group (TG), and Training + supplement group (TSG). Following baseline measurements, the two training groups (TG and TSG) started the 12 weeks of exercise training program (3 sessions per week). A total of 36 sessions lasting up to 60 min were included in the HIFT program using the CrossFit program. The eligible participants received 5 g/day of thylakoid-rich spinach extract or matching placebo as 5 g/day of raw corn starch (one sachet, 30 min before lunch) for 12 weeks. Baseline assessments were obtained 48 hours before the start of the training protocols and 48 hours after the last training session in all groups. There were significant interactions (p<0.001 for all) between exercise and time for adiponectin (ES:0.48), leptin (ES:0.46), resistin (ES:0.3), omentin (ES:0.65), vaspin (ES:0.46), visfatin (ES:0.62), apelin (ES:0.42), RBP4 (ES:0.63), chemrin (0.36) and semaphorin3c (ES: 0.5). Plasma levels of semaphorin3c were significantly correlated (p<0.05) with body weight (r= 0.57), BMI (r= 0.43), FFM (r= -0.612), FAT (r= 0.768), VO2peak (r=-0.53), insulin (r= 0.756), glucose (r= 0.623), and HOMA-IR (r= 0.727). There were also significant group differences in insulin (ES: 0.77), glucose (ES: 0.21), and HOM-IR (ES: 0.44) (p<0.05). Our findings indicate that 12 weeks of HIFT supplemented with spinach-derived thylakoid reduced levels of leptin, resistin, vaspin, visfatin, apelin, RBP4, chemrin, semaphorin3c and insulin resistance while increasing adiponectin and omentin levels in men with obesity.